Biofunctionalization of titanium surfaces with alendronate and albumin modulates osteoblast performance - Albano, Carolina Simão [UNESP]; Moreira Gomes, Anderson [UNESP]; da Silva Feltran, Geórgia [UNESP]; da Costa Fernandes, Célio Junior [UNESP]; Trino, Luciana Daniele [UNESP]; Zambuzzi, Willian Fernando [UNESP]; Lisboa-Filho, Paulo Noronha [UNESP] (Elsevier, 2020)
Background: Biofunctionalization of titanium surfaces can improve host responses, especially considering the time for osteointegration and patient recovery. This prompted us to modify titanium surfaces with alendronate and albumin and to investigate the behavior of osteoblasts on these surfaces. Methods: The biofunctionalization of titanium surfaces was characterized using classical physicochemical approaches and later used to challenge pre-osteoblast cells up to 24 h. Then their viability and molecular behavior were investigated using mitochondrial dehydrogenase activity and RTq-PCR technologies, respectively. Potential stimulus of extracellular remodeling was also investigated by zymography. Results: Our data indicates a differential behavior of cells responding to the surfaces, considering the activity of mitochondrial dehydrogenases. Molecularly, the differential expression of genes related with cell adhesion highlighted the importance of Integrin-β1, Fak, and Src. These 3 genes were significantly decreased in response to titanium surfaces modified with alendronate, but this behavior was reverted when alendronate was associated with albumin. Alendronate-modified surfaces promoted a significant increase on ECM remodeling, as well as culminating with greater gene activity related to the osteogenic phenotype (Runx2, Alp, Bsp). Conclusion: Altogether, our study found interesting osteogenic behavior of cells in response to alendronate and albumin surfaces, which indicates the need for in vivo analyses to better consider these surfaces before clinical trials within the biomedical field.

Materials science; Cell biology; Implants; Biocompatibility; Trace elements; Osseointegration; Bisphosphonate; Albumin.
Keywords: Albumin; Biocompatibility; Bisphosphonate; Cell biology; Implants; Materials science; Osseointegration; Trace elements